Pharmacological inhibition of RUNX1 reduces infarct size after acute myocardial infarction in rats and underlying mechanism revealed by proteomics implicates repressed cathepsin levels - Hengshu Chen; Si Wang; Xiaoling Zhang; Xing Hua; Meng Liu; Yanan Wang; Simiao Wu; Weihong He (Functional & Integrative Genomics, 2024)
Myocardial infarction (MI) results in prolonged ischemia and the subsequent cell death leads to heart failure which is linked to increased deaths or hospitalizations. New therapeutic targets are urgently needed to prevent cell death and reduce infarct size among patients with MI. Runt-related transcription factor-1 (RUNX1) is a master-regulator transcription factor intensively studied in the hematopoietic field. Recent evidence showed that RUNX1 has a critical role in cardiomyocytes post-MI. The increased RUNX1 expression in the border zone of the infarct heart contributes to decreased cardiac contractile function and can be therapeutically targeted to protect against adverse cardiac remodelling. This study sought to investigate whether pharmacological inhibition of RUNX1 function has an impact on infarct size following MI. In this work we demonstrate that inhibiting RUNX1 with a small molecule inhibitor (Ro5-3335) reduces infarct size in an in vivo rat model of acute MI. Proteomics study using data-independent acquisition method identified increased cathepsin levels in the border zone myocardium following MI, whereas heart samples treated by RUNX1 inhibitor present decreased cathepsin levels. Cathepsins are lysosomal proteases which have been shown to orchestrate multiple cell death pathways. Our data illustrate that inhibition of RUNX1 leads to reduced infarct size which is associated with the suppression of cathepsin expression. This study demonstrates that pharmacologically antagonizing RUNX1 reduces infarct size in a rat model of acute MI and unveils a link between RUNX1 and cathepsin-mediated cell death, suggesting that RUNX1 is a novel therapeutic target that could be exploited clinically to limit infarct size after an acute MI.